Rock strength analysis due to discontinuity and grouting - Nur Alam Syah Rahman; Ganda Marihot Simangunsong; Irwandi Arif (Indonesian Mining Professionals Journal, 2020)
Instability on rock, one of many factors caused by joint. Decreased of rock strength occurred inline with existence a number of joints. Poor rock have a large number of joints. Therefore rock reinforcement such as grouting can be one of the solution. This research conducted on artificial sample Moldano Tara (dental stone type III). It had been given artificial joints with orientation 60o from axial and frequency 1 till 2.  Furthermore, grout material with composition 4C;5W had been injected on joint and cured in 28 days. Triaxial test are done in all samples intact, jointed and grouted and its been analyzed with Mohr-Coulomb and Hoek Brown failure criteria. It is found,  joint given negative contribution on shear strength, declining 65,75% and 73,48%, whereas on UCS declined 46,85% dan 56,19%. On the other hand, grouting had been given positive contribution on shear strength, increasing 166,15% and 188,07%, while UCS increased 46,60% and 60,92%